2007
DOI: 10.1093/ajcn/86.4.1054
|View full text |Cite
|
Sign up to set email alerts
|

Calcium requirements: new estimations for men and women by cross-sectional statistical analyses of calcium balance data from metabolic studies

Abstract: The findings suggest that the calcium requirement for men and women is lower than previously estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 31 publications
3
90
0
Order By: Relevance
“…In a large series of calcium balance studies, Hunt and Johnson reported that neutral calcium balance occurred at a much lower calcium intake (741 mg/d) than reported by Heaney and colleagues, and also was not altered by age or sex (89). Although longer than previous studies (each balance study had a minimum duration of 16 days), nevertheless these studies still may not be long enough for adaptation to a change in calcium intake.…”
Section: Later Researchmentioning
confidence: 83%
“…In a large series of calcium balance studies, Hunt and Johnson reported that neutral calcium balance occurred at a much lower calcium intake (741 mg/d) than reported by Heaney and colleagues, and also was not altered by age or sex (89). Although longer than previous studies (each balance study had a minimum duration of 16 days), nevertheless these studies still may not be long enough for adaptation to a change in calcium intake.…”
Section: Later Researchmentioning
confidence: 83%
“…All of these values, from 300 mg daily during the third trimester to 120 mg daily during late lactation, may seem achievable given normal intake of calcium and normal efficiency of intestinal calcium absorption. However, fractional calcium absorption is normally ϳ25% of intake in healthy adults who consume adequate calcium (420). If normal efficiency of intestinal calcium absorption were relied upon, pregnant women would have to consume an extra 1,200 mg/day during the third trimester, whereas lactating women would have to consume an extra 800 mg daily during the first 6 mo and 480 mg daily during the second 6 mo.…”
Section: Introductionmentioning
confidence: 99%
“…In our study this can be achieved easily with calcium supplements of 1000 mg/d in 12% of the patients with lowest baseline calcium intake and with 500 mg/d in 56% of the patients with moderate baseline calcium intake, while 31% did not need calcium supplementation. It is of interest that cross-sectional studies show that a neutral calcium balance is achieved at an intake of 741 mg/day of calcium [15]; and that, if vitamin D serum levels are adequate, the need of total calcium intake would be lower than 1000 mg/d [44]. However, such hypotheses still need to be tested prospectively.…”
Section: Need Of Calcium and Vitamin D In Patients After A Recent Framentioning
confidence: 99%
“…Therefore, medical therapy is advocated in fracture patients at high risk of subsequent fractures, including drug therapy and adequate intake of calcium and vitamin D [9][10][11][12][13]. Regardless of fracture history, calcium intake is low in subjects older than 50 years, in the elderly and in patients with osteoporosis [14][15][16]. Vitamin D insufficiency (serum 25(OH)D concentration <50 nmol/l) is endemic worldwide [17] and is frequently present in patients with osteoporosis, with or without a fracture [18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%